Exploring the gap between perfect Bayesian equilibrium and sequential equilibrium - Giacomo Bonanno (University of California, Department of Economics, 2016)
In (5) a solution concept for extensive-form games was introduced, called perfect Bayesian equilibrium (PBE), and shown to be a strict refinement of subgame-perfect equilibrium; it was also shown that, in turn, sequential equilibrium (SE) is a strict refinement of PBE. In (6) the notion of PBE was used to provide a characterization of SE in terms of a strengthening the two defining components of PBE (besides sequential rationality), namely AGM consistency and Bayes consistency. In this paper we explore the gap between PBE and SE by identifying solution concepts that lie strictly between PBE and SE; these solution concepts embody a notion of "conservative" belief revision. Furthermore, we provide a method for determining if a plausibility order on the set of histories is choice measurable, which is a necessary condition for a PBE to be a SE.
Keywords: 330